1990
DOI: 10.1089/aid.1990.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 in Monocyte/Macrophage Cultures by 2′,3′-Dideoxycytidine-5′-Triphosphate, Free and in Liposomes*

Abstract: The antiviral effects of 2',3'-dideoxycytidine (ddC), 2',3'-dideoxycytidine-5'-triphosphate (ddCTP) and liposome-encapsulated ddCTP [L(ddCTP)] were compared in cultured human monocyte-macrophages (M/M) infected with HIV-1. These treatments inhibited virus replication at nanomolar drug levels with activities in the order ddC greater than ddCTP = L(ddCTP). Studies on drug stability and uptake suggest that a large part of the free ddCTP is dephosphorylated before entering the cells, whereas L(ddCTP) remains stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In general, this physically controlled release method could be complementary to any other drug delivery and tagging mechanism, whether it is physical or chemical. Although AZTTP is used in the experiment, the ability of on-demand drug release by a MEN nano-carrier discovered in this study is also relevant to the treatment of other diseases such as many CNS diseases, cancer and others, where deep-tissue high-efficacy drug delivery at the sub-cellular level is key 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this physically controlled release method could be complementary to any other drug delivery and tagging mechanism, whether it is physical or chemical. Although AZTTP is used in the experiment, the ability of on-demand drug release by a MEN nano-carrier discovered in this study is also relevant to the treatment of other diseases such as many CNS diseases, cancer and others, where deep-tissue high-efficacy drug delivery at the sub-cellular level is key 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as it is related to the delivery across the BBB, this approach provides a way to deliver drugs sufficiently fast to avoid their engulfing by the reticuloendothelial system. Nucleotide reverse transcriptase inhibitor 3 0 -azido-3 0 -deoxythymidine-5 0 -triphosphate (AZTTP) is among the most challenging anti-retroviral drugs to deliver across the BBB 12,13 . Previously we have shown that MNs tagged with AZTTP transmigrated across the BBB by the application of an external magnetic field without affecting the integrity of the BBB, and the transmigrated AZTTP demonstrated significant inhibition of HIV-1 p24 antigen production in an in vitro infection model system compared with the free AZTTP 14 .…”
mentioning
confidence: 99%
“…Broadly, there are four types of the liposomes mainly studied for the anti-HIV/AIDS drug delivery; these are cationic, anionic, sterically stabilized and immunoliposomes [18]. Encapsulated 2' ,3'-dideoxycytidine-5'-triphosphate in liposomes and compared its antiviral effect with the dideoxycytidine and dideoxycytidine-triphosphate in cultured human monocyte-macrophages infected with HIV-1 [93]. The antiviral effect and bone marrow toxicity of AZT-loaded liposomes in C57BL/6 mice Zidovudine was exploited by Phillips and co-workers [94].…”
Section: Dendrimersmentioning
confidence: 99%
“…Studies have been performed in order to overcome the phosphorylation step which is not feasible due to the presence of phosphatases which hydrolyse nucleotides into the corresponding nucleosides and to the poor permeability of cell membranes to the phosphatase form [114]. Thus, the phosphorylated form of zalcitabin was employed in order to overcome these limitations and to obtain site specific delivery [93]. This nanoformulation was investigated in humanmonocyte/macrophages infected with HIV-1.…”
Section: Dendrimersmentioning
confidence: 99%
“…Incubation was terminated by washing the suspended or adhered cells three times in ice-cold phosphate-buffered saline and lysing them with trichloroacetic acid. Details of the extraction process and analysis of the neutralized acid extract by high-pressure liquid chromatography (HPLC) are described elsewhere (1,13). Control experiments with [3H]AZT triphosphate (20 Ci/mmol; Moravek) revealed that the AZT phosphates remained unchanged during the preparative procedures described above.…”
mentioning
confidence: 99%